Graphene thermal pad and method of making the same
Patent Information
- Application Number
- CN202611269151.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-20
- Publication Date
- 2026-10-27
AI Technical Summary
但现有定向叠层石墨烯导热垫片存在显著的结构力学缺陷:材料叠层方向整体强度较差,实际使用及加工装配过程中极易发生开裂失效
[0033]为更好地说明本发明的目的、技术方案和有益效果,下面将结合具体实施例对本发明作进一步说明。需说明的是,下述实施所述方法是对本发明做的进一步解释说明,不应当作为对本发明的限制。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of thermal interface materials technology, and in particular to a graphene thermal conductive pad and its preparation method. Background Technology
[0002] With the continuous improvement of integration and operating power in 5G communication, high-power chips, and new energy power devices, the heat flux density per unit area of electronic devices is increasing dramatically, placing stringent requirements on the vertical thermal conductivity, structural stability, and assembly compatibility of thermal interface materials. Traditional silicone thermal pads and ceramic-filled thermal conductive materials are limited by the intrinsic thermal conductivity of the filler and the disordered structural characteristics, making it difficult to improve their vertical thermal conductivity and meet the high-efficiency heat dissipation requirements of high-end high-power devices. As a new generation of high-performance thermal interface material, oriented stacked graphene thermal pads can construct continuous and interconnected vertical thermal conduction channels by stacking graphene films in the Z-direction of thickness, bonding and curing them, and then cutting them into shapes. The material has a high Z-direction thermal conductivity and has a heat dissipation capacity that far exceeds that of traditional thermal pads, making it extremely valuable for applications in the field of thermal management of high-end electronic devices. However, existing oriented multilayer graphene thermal pads have significant structural and mechanical defects: the overall strength along the stacked material is poor, making them highly susceptible to cracking and failure during actual use and assembly. Experimental verification has shown that the core failure mechanism of this type of material is not interfacial debonding between the graphene film and the silicone adhesive layer, but rather intralayer tearing caused by insufficient strength of the graphene film itself. This manifests as peeling defects during material cutting, brittle fracture under Z-axis tensile conditions, and large-angle buckling and deflection of the graphene sheets under compressive loads, severely reducing product yield and long-term service reliability. Currently, to address the poor mechanical properties of multilayer graphene gaskets, the mainstream technical solutions focus on creating arrays of stacked through-holes and combining them with reinforcing fillers for composite modification. For example, a technical solution using a through-hole structure combined with carbon fiber filler pinning reinforcement improves the interlayer bonding force through physical anchoring, thus mitigating the problem of gasket delamination and cracking.
[0003] However, this type of through-hole reinforcement solution has unavoidable technical drawbacks, making it difficult to balance the comprehensive performance of material thermal conductivity, mechanical properties, and assembly compatibility. First, the through-hole directly interrupts the continuous Z-channel thermal conductivity of graphene. The thermal conductivity of the colloid or carbon fiber filling the pores is far lower than that of graphene, causing a 15-40% loss in the Z-channel thermal conductivity of the material, completely sacrificing the core advantage of high thermal conductivity in oriented stacked graphene materials. Second, this solution can only improve the interlayer anti-delamination ability, without improving the fundamental failure problem of tearing within the graphene film. Defects such as material peeling during cutting, tensile brittle fracture, and compression deflection still exist. Third, the colloid filling of the through-hole significantly reduces the internal porosity of the material, causing the gasket compression rebound rate to drop drastically from 30-40% to below 20%, losing the flexible fitting ability of the thermal interface material to adapt to the surface warping and assembly tolerances of the component, greatly limiting the actual application scenarios of the product. In summary, current commercially available oriented multilayer graphene thermal pads generally suffer from a technical bottleneck where high thermal conductivity cannot be reconciled with structural strength and compression resilience. Existing modification techniques fail to fundamentally solve the problem of intralayer tearing in graphene films and severely compromise the material's core thermal conductivity and flexible assembly characteristics. Therefore, developing a graphene thermal pad that preserves the complete Z-axis graphene thermal conductivity pathway, eliminates intralayer tearing failure, and simultaneously possesses excellent compression resilience is a pressing technical problem that needs to be solved by those skilled in the art. Summary of the Invention
[0004] Based on the above problems, the purpose of this invention is to provide a graphene thermal conductive pad and its preparation method. This graphene thermal conductive pad can specifically improve the intrinsic layer strength of the graphene foam film skeleton without sacrificing the thermal conductivity and compression resilience of the graphene foam film, thereby achieving the effects of anti-slip of the sheet, anti-fracture of the node, and anti-tear of the pore wall. It can fundamentally solve the failure problems of cutting peeling, Z-direction tensile brittle fracture, and compression buckling deflection.
[0005] To achieve the above objectives, the first aspect of the present invention provides a graphene thermal conductive pad, comprising N stacked composites, where N is an integer greater than or equal to 100. The composite is formed by stacking a first silicone layer, a composite graphene foam film, and a second silicone layer. The composite graphene foam film is a graphene foam film with aramid nanofibers adsorbed on its framework. Along the stacking direction of the composites, the content of aramid nanofibers in the M middle composites is lower than that in the composites at both ends, where M is an integer of 0.80 to 0.95 times N.
[0006] The composite graphene foam membrane of this invention is a graphene foam membrane with aramid nanofibers adsorbed on its framework. The graphene foam membrane is a porous framework composed of three-dimensionally interconnected graphene sheets. The basic structural units of the framework are pore walls (curved surfaces formed by bending graphene sheets) and nodes (three-way or multi-way points where three or more sheets intersect). The aramid nanofibers are adsorbed onto the framework of the graphene foam membrane, rather than being directly embedded in the framework or having open pores in the framework. This has a relatively small impact on the blockage of the Z-direction thermal channels of the graphene foam membrane. Furthermore, the flexible segments of the aramid nanofibers can bridge cracks and deflect fracture paths, providing a strong toughening effect on the brittle framework of the graphene foam membrane. Therefore, without affecting the thermal conductivity and compression resilience of the graphene foam membrane, the aramid nanofibers can also improve the intrinsic layer strength of the framework, making the sheets resistant to slippage, the nodes resistant to fracture, and the pore walls resistant to tearing. Furthermore, the aramid nanofiber content in the graphene thermal pad is low in the middle and high at both ends. This gradient concentration design allows the high-content aramid nanofibers at both ends to withstand the lateral or shear forces generated during the cutting process, while the middle section experiences less cutting force. The low content satisfies strength requirements while also reducing interfacial thermal resistance. Therefore, the gradient concentration design allows different positions within the graphene thermal pad composite to perform different functions, resolving the conflict between strength and thermal conductivity in subsequent Z-axis cutting scenarios.
[0007] As a technical solution of the present invention, the first silicone layer and the second silicone layer have the same composition, and the raw materials include 15 to 40 parts of vinyl silicone oil, 2 to 8 parts of hydrogen-containing silicone oil, 500 to 2000 ppm of platinum catalyst and 50 to 200 ppm of inhibitor.
[0008] As one technical solution of the present invention, the vinyl silicone oil is a vinyl-terminated silicone oil with a viscosity of 200~500 cps, the hydrogen content of the hydrogen-containing silicone oil is 0.3~0.6 wt.%, and the inhibitor is selected from at least one of 2-methyl-3-butyn-2-ol, 3,5-dimethyl-1-hexyn-3-ol, 2-phenyl-3-butyn-2-ol, 1-ethynylcyclohexanol, 3-methyl-1-penten-4-yn-3-ol, and 3,5-dimethyl-3-hexen-1-yn.
[0009] As one technical solution of the present invention, the specific surface area of the graphene foam film is 300~1200m². 2 / g, with a volume fraction of mesopores of 2~50nm ≥60%, a thickness of 100~500μm, and an areal density of 10~50mg / cm³. 2 .
[0010] As one technical solution of the present invention, the aramid nanofibers have a diameter of 10~100nm, an aspect ratio of 1000~5000:1, and a specific surface area of 50~600m². 2 / g.
[0011] As one technical solution of the present invention, the Z-direction thermal conductivity is ≥130W / m·K, the interlaminar tensile strength is ≥0.06MPa, the compression ratio at 50psi is ≥40%, and the overall cutting yield is ≥98%.
[0012] The second aspect of this invention provides a method for preparing a graphene thermal conductive pad, comprising the following steps: (I) Plasma cleaning The surfaces of N graphene foam films are plasma cleaned until Ra≤50% to obtain activated graphene foam films, where N is an integer greater than or equal to 100. (II) Impregnated aramid nanofiber dispersion First, a first aramid nanofiber dispersion with a concentration of 0.05~0.50 mg / mL and a second aramid nanofiber dispersion with a concentration of 1.5~3.0 mg / mL are prepared. M activated graphene foam films are impregnated in the first aramid nanofiber dispersion to obtain a first impregnated graphene foam film. The remaining activated graphene foam films are impregnated in the second aramid nanofiber dispersion to obtain a second impregnated graphene foam film. M is an integer multiple of N, ranging from 0.80 to 0.95. (III) Drying and shaping The first impregnated graphene foam film and the second impregnated graphene foam film were freeze-dried and then heat-treated to obtain the first composite graphene foam film and the second composite graphene foam film, respectively. (IV) Stacking and curing Both surfaces of each of the first composite graphene foam films and each of the second composite graphene foam films are coated with silicone liquid. Then, all the first composite graphene foam films are stacked along the opposite direction of the surfaces to obtain a first intermediate body. All the second composite graphene foam films are divided into two parts and stacked on both ends of the first intermediate body along the same stacking direction. Then, they are hot-pressed and cured to obtain a second intermediate body. (V) Z-axis cutting The second intermediate is cut along the stacking direction to obtain a graphene thermal pad.
[0013] In the preparation method of the graphene thermal conductive pad of the present invention, the surface of the graphene foam film is first plasma cleaned until Ra≤50%, thereby activating the surface of the graphene foam film (containing oxygen-containing functional groups such as -OH or C=O) by removing contaminants rather than deep etching. After impregnation with aramid nanofiber dispersion, freeze-drying and then heat treatment are performed. The benzene rings of the main chain in the aramid nanofiber form π-π stacks with the six-membered rings of graphene, and the amide bonds form hydrogen bonds with the oxygen-containing functional groups. This allows the aramid nanofibers to be adsorbed on the curved surface of the pore walls and the triangular nodes of the graphene foam film. It is not a direct embedding into the skeleton or a through-hole in the skeleton, so it has little impact on the blockage of the Z-direction thermal channels of the graphene foam film. Therefore, without affecting the thermal conductivity and compression resilience of the graphene foam film, the aramid nanofibers can also improve the intrinsic strength of the skeleton. After stacking and curing, an overlap of a silicone layer, a graphene foam film with adsorbed aramid nanofibers, and a silicone layer is formed. The content of aramid nanofibers in this overlap is lower in the middle and higher at both ends. When cut in the Z-direction, the higher content of aramid nanofibers at both ends can withstand the lateral or shear forces generated during cutting. Therefore, the preparation method of this invention can produce a graphene thermally conductive pad that improves the intrinsic intralayer strength of the graphene foam film skeleton without sacrificing the thermal conductivity and compression resilience of the graphene foam film.
[0014] As one technical solution of the present invention, the specific surface area of the graphene foam film is 300~1200m². 2 / g, with a volume fraction of mesopores of 2~50nm ≥60%, a thickness of 100~500μm, and an areal density of 10~50mg / cm³. 2 .
[0015] As a technical solution of the present invention, the plasma cleaning is carried out using a plasma cleaning machine, wherein the volume ratio of Ar / O2 in the plasma cleaning machine is 5~10:1, the RF power is 50~200W, the gas pressure is 50~200Pa, the time is 5~30s, and the water-cooled backplate is <80℃.
[0016] As a technical solution of the present invention, the first aramid nanofiber dispersion and the second aramid nanofiber dispersion comprise aramid nanofibers, a solvent, and an inorganic alkali. The aramid nanofibers have a diameter of 10-100 nm, an aspect ratio of 1000-5000:1, and a specific surface area of 50-600 m². 2 / g, wherein the solvent is an ethanol-water mixture, dimethyl sulfoxide, or dimethylformamide, the inorganic base is potassium hydroxide or sodium hydroxide, and the mass ratio of the inorganic base to the aramid nanofiber is 0.5~3.0:1.
[0017] As a technical solution of the present invention, the immersion time of the activated graphene foam film in the first ANF dispersion is 10~30s, and the immersion time of the activated graphene foam film in the second ANF dispersion is 30~90s, and the immersion is repeated 2~3 times.
[0018] As one technical solution of the present invention, the freeze-drying temperature is -50~-30℃ and the time is 6~24h.
[0019] As one technical solution of the present invention, the heat treatment is carried out in an inert atmosphere at a temperature of 200~280℃ for 1~2 hours.
[0020] As a technical solution of the present invention, the hot pressing curing is a gradient temperature curing method, first heating to 70~100℃ and 80~120psi and holding for 0.5~2.0h, then heating to 110~135℃ and 130~160psi and holding for 0.5~2.0h, maintaining pressure and then heating to 140~160℃ and holding for 15~60min.
[0021] As a technical solution of the present invention, the Z-axis cutting is performed using diamond wire cutting, wherein the wire diameter of the diamond wire cutting is 0.20~0.35mm, the particle size is 30~60μm, the speed is 0.3~0.8mm / min, and the tension is 15~25N.
[0022] As a technical solution of the present invention, the Z-axis cutting is followed by double-sided polishing, and the polishing is performed until the pad thickness is 0.2~0.5mm.
[0023] As one technical solution of the present invention, the raw materials of the silicone liquid include 15-40 parts of vinyl silicone oil, 2-8 parts of hydrogen-containing silicone oil, 500-2000 ppm of platinum catalyst and 50-200 ppm of inhibitor.
[0024] As one technical solution of the present invention, the vinyl silicone oil is a vinyl-terminated silicone oil with a viscosity of 200~500 cps, the hydrogen content of the hydrogen-containing silicone oil is 0.3~0.6 wt.%, and the inhibitor is selected from at least one of 2-methyl-3-butyn-2-ol, 3,5-dimethyl-1-hexyn-3-ol, 2-phenyl-3-butyn-2-ol, 1-ethynylcyclohexanol, 3-methyl-1-penten-4-yn-3-ol, and 3,5-dimethyl-3-hexen-1-yn.
[0025] As one technical solution of the present invention, the viscosity of the silica gel liquid at 25°C is 2000~8000cps.
[0026] As a technical solution of the present invention, the silicone liquid is applied to both surfaces of the first composite graphene foam film or the second composite graphene foam film by a doctor blade or a micro-gravure roller, with a wet thickness of 20~200μm. Detailed Implementation
[0027] The graphene thermal pad of the present invention has a Z-direction thermal conductivity ≥130W / m·K, interlayer tensile strength ≥0.06MPa, compression ratio ≥40% at 50psi, and overall cutting yield ≥98%. It can simultaneously achieve thermal conductivity, strength and compression ratio, and has a high cutting yield, making it suitable for industrial production. This meets the demand for high-performance thermal interface materials in fields such as 5G communication, high-power chips, and new energy power devices.
[0028] The graphene thermal conductive pad of the present invention comprises N stacked composites, where N is an integer greater than or equal to 100. Each composite is formed by stacking a first silicone layer, a composite graphene foam film, and a second silicone layer. The composite graphene foam film is a graphene foam film with aramid nanofibers adsorbed on its framework. Along the stacking direction of the composites, the content of aramid nanofibers in the M composites located in the middle is lower than that in the composites at both ends, where M is an integer of 0.80 to 0.95 times N. Further, N can be 500, M can be 400 to 475, and the content of aramid nanofibers in the 20 to 100 composites at both ends of the graphene thermal conductive pad is low. The number of composites with low aramid nanofiber content can be the same or different, but the number at the end closer to the Z-direction cut cannot be less than that at the other end.
[0029] Furthermore, the first and second silicone layers have identical compositions, and the raw materials include 15-40 parts vinyl silicone oil, 2-8 parts hydrogen-containing silicone oil, 500-2000 ppm platinum catalyst, and 50-200 ppm inhibitor. The vinyl silicone oil is a terminal vinyl silicone oil with a viscosity of 200-500 cps. The hydrogen content of the hydrogen-containing silicone oil is 0.3-0.6 wt.%. The inhibitor is selected from at least one of 2-methyl-3-butyn-2-ol, 3,5-dimethyl-1-hexyn-3-ol, 2-phenyl-3-butyn-2-ol, 1-ethynylcyclohexanol, 3-methyl-1-penten-4-yn-3-ol, and 3,5-dimethyl-3-hexen-1-yn. The platinum catalyst can be a platinum-based catalyst commonly used in hydrosilylation reactions. The specific surface area of the graphene foam film is 300-1200 m². 2 / g, with a volume fraction of mesopores of 2~50nm ≥60%, a thickness of 100~500μm, and an areal density of 10~50mg / cm³. 2 Aramid nanofibers have a diameter of 10-100 nm, an aspect ratio of 1000-5000:1, and a specific surface area of 50-600 m². 2 / g.
[0030] The method for preparing the graphene thermal pad of the present invention includes the following steps: (I) Plasma cleaning The surfaces of N graphene foam films are plasma cleaned until Ra≤50% to obtain activated graphene foam films, where N is an integer greater than or equal to 100. (II) Impregnated aramid nanofiber dispersion First, a first aramid nanofiber dispersion with a concentration of 0.05~0.50 mg / mL and a second aramid nanofiber dispersion with a concentration of 1.5~3.0 mg / mL are prepared. M activated graphene foam films are impregnated in the first aramid nanofiber dispersion to obtain a first impregnated graphene foam film. The remaining activated graphene foam films are impregnated in the second aramid nanofiber dispersion to obtain a second impregnated graphene foam film. M is an integer multiple of N, ranging from 0.80 to 0.95. (III) Drying and shaping The first impregnated graphene foam film and the second impregnated graphene foam film were freeze-dried and then heat-treated to obtain the first composite graphene foam film and the second composite graphene foam film, respectively. (IV) Stacking and curing The two surfaces of each first composite graphene foam film and each second composite graphene foam film are coated with silicone liquid. Then, all the first composite graphene foam films are stacked along the opposite direction of the surfaces to obtain the first intermediate. All the second composite graphene foam films are divided into two parts and stacked on both ends of the first intermediate along the same stacking direction. Then, they are hot-pressed and cured to obtain the second intermediate. (V) Z-axis cutting The second intermediate is cut along the stacking direction to obtain a graphene thermal pad.
[0031] Among them, the specific surface area of graphene foam film is 300~1200m². 2 / g, with a volume fraction of mesopores of 2~50nm ≥60%, a thickness of 100~500μm, and an areal density of 10~50mg / cm³. 2 The first and second aramid nanofiber dispersions comprise aramid nanofibers, a solvent, and an inorganic alkali. The aramid nanofibers have a diameter of 10–100 nm, an aspect ratio of 1000–5000:1, and a specific surface area of 50–600 m². 2 / g. The solvent is an ethanol-water mixture, dimethyl sulfoxide, or dimethylformamide. The inorganic base is potassium hydroxide or sodium hydroxide, with a mass ratio of inorganic base to aramid nanofibers of 0.5~3.0:1. The addition of the inorganic base deprotonates and dissociates the aramid nanofibers, ensuring stable dispersion. The dispersion prepared using an ethanol-water mixture, dimethyl sulfoxide, or dimethylformamide is stable and has an adjustable concentration, suitable for gradient impregnation. Aramid nanofibers can be sourced from Kevlar industrial scraps, resulting in lower costs. The raw materials for the silica gel solution include 15~40 parts vinyl silicone oil, 2~8 parts hydrogen-containing silicone oil, 500~2000 ppm platinum catalyst, and 50~200 ppm inhibitor. The vinyl silicone oil is a vinyl-terminated silicone oil with a viscosity of 200-500 cps. The hydrogen content of the hydrogen-containing silicone oil is 0.3-0.6 wt.%, and the inhibitor is selected from at least one of 2-methyl-3-butyn-2-ol, 3,5-dimethyl-1-hexyn-3-ol, 2-phenyl-3-butyn-2-ol, 1-ethynylcyclohexanol, 3-methyl-1-penten-4-yn-3-ol, and 3,5-dimethyl-3-hexen-1-yne. The viscosity of the silica gel liquid at 25°C is 2000-8000 cps.
[0032] In the plasma cleaning machine, the Ar / O2 volume ratio is 5~10:1, the RF power is 50~200W, the gas pressure is 50~200Pa, the time is 5~30s, and the water-cooled backplate is below 80℃. The activated graphene foam film is immersed in the first ANF dispersion for 10~30s, and then immersed in the second ANF dispersion for 30~90s, repeated 2~3 times. Freeze-drying is performed at -50~-30℃ for 6~24h. Heat treatment is carried out under an inert atmosphere at 200~280℃ for 1~2h. Hot-press curing is a gradient temperature curing process. First, the temperature is raised to 70-100℃ and held at 80-120psi for 0.5-2.0 hours. Then, the temperature is raised to 110-135℃ and held at 130-160psi for 0.5-2.0 hours. While maintaining pressure, the temperature is raised again to 140-160℃ and held for 15-60 minutes. Silica gel is applied to both surfaces of the first or second composite graphene foam film using a doctor blade or microgravure roller, with a wet thickness of 20-200 μm. The second composite graphene foam film can be divided into two parts, either evenly or unevenly, and stacked at both ends of the first intermediate body. However, the number of second composite graphene foam films near the Z-axis cut end must not be less than that at the other end. Z-axis cutting is performed using diamond wire cutting with a wire diameter of 0.20~0.35mm, a particle size of 30~60μm, a cutting speed of 0.3~0.8mm / min, and a tension of 15~25N. After Z-axis cutting, double-sided polishing is performed until the pad thickness is 0.2~0.5mm.
[0033] To better illustrate the purpose, technical solution, and beneficial effects of this invention, the invention will be further described below with reference to specific embodiments. It should be noted that the methods described below are further explanations of this invention and should not be construed as limiting it.
[0034] Example 1 This embodiment is a graphene thermal conductive pad comprising 500 stacked composites. Each composite is formed by stacking a first silicone layer, a composite graphene foam film, and a second silicone layer. The composite graphene foam film is a graphene foam film with aramid nanofibers adsorbed onto its framework. Along the stacking direction of the composites, the content of aramid nanofibers in the 450 composites located in the middle is lower than that in the composites at both ends. The raw materials for the first and second silicone layers include 25 parts of vinyl-terminated silicone oil (viscosity 350 cps), 3 parts of hydrogen-containing silicone oil (hydrogen content 0.5 wt.%), 1200 ppm platinum catalyst, and 100 ppm 2-methyl-3-butyn-2-ol. The specific surface area of the graphene foam film is 620 m². 2 / g, with mesopores having a pore size of 2~50nm accounting for 67% of the volume, an area of 150×150mm, a thickness of 180μm, and an areal density of 26mg / cm³. 2 The aramid nanofibers are Kevlar 49 (400D), with a diameter of 50 nm, an aspect ratio of 2000:1, and a specific surface area of 350 m². 2 / g.
[0035] The preparation method of this graphene thermal pad includes the following steps: (I) Plasma cleaning Activated graphene foam films were obtained by plasma cleaning of the surfaces of N graphene foam films until Ra ≤ 50%. The cleaning was performed using a plasma cleaner with an Ar / O2 volume ratio of 5:1, an RF power of 100W, a gas pressure of 80Pa, a time of 15s, and a water-cooled backplate temperature of <80℃.
[0036] (II) Impregnated aramid nanofiber dispersion 2.0 g of aramid nanofibers, 1.2 g of potassium hydroxide, and 100 mL of dimethyl sulfoxide were reacted at 80 °C for 5 days to obtain a dispersion with a concentration of 20 mg / mL. Diluted with dimethyl sulfoxide, a first aramid nanofiber dispersion with a concentration of 0.15 mg / mL and a second aramid nanofiber dispersion with a concentration of 3.0 mg / mL were obtained. 450 activated graphene foam films were immersed in the first aramid nanofiber dispersion for 30 s to obtain a first impregnated graphene foam film. The remaining 50 activated graphene foam films were immersed in the second aramid nanofiber dispersion for 60 s, and this immersion was repeated twice to obtain a second impregnated graphene foam film.
[0037] (III) Drying and shaping The first and second impregnated graphene foam films were freeze-dried at -45°C for 18 hours, and then imidized at 200°C under a nitrogen atmosphere for 1.5 hours to obtain the first composite graphene foam film and the second composite graphene foam film, respectively.
[0038] (IV) Stacking and curing Vinyl-terminated silicone oil, hydrogen-containing silicone oil, platinum catalyst, and 2-methyl-3-butyn-2-ol were mixed and degassed to a silica gel solution with a viscosity of 4820 cps. The silica gel solution was then applied to both surfaces of each first and second composite graphene foam film using a scraper, with a wet thickness of 80 µm. 450 first composite graphene foam films were then stacked along opposite directions to obtain a first intermediate. 50 second composite graphene foam films were divided into two equal parts and stacked at both ends of the first intermediate along the same stacking direction. The mixture was first heated to 80°C and held at 100 psi for 1.0 h, then heated to 120°C and held at 150 psi for 1.0 h, and then heated to 150°C and held for 30 min while maintaining pressure to obtain the second intermediate.
[0039] (V) Z-axis cutting The second intermediate was cut with diamond wire parallel to the stacking direction and then polished to a thickness of 0.3 mm to form a graphene thermal pad. The diamond wire diameter was 0.20 mm, the particle size was 50 μm, the cutting speed was 0.5 mm / min, and the tension was 20 N.
[0040] Example 2 This embodiment is a graphene thermal conductive pad comprising 700 stacked composites. Each composite is formed by stacking a first silicone layer, a composite graphene foam film, and a second silicone layer. The composite graphene foam film is a graphene foam film with aramid nanofibers adsorbed onto its framework. Along the stacking direction of the composites, the content of aramid nanofibers in the 600 composites located in the middle is lower than that in the composites at both ends. The raw materials for the first and second silicone layers include 35 parts of vinyl-terminated silicone oil (viscosity 400 cps), 6 parts of hydrogen-containing silicone oil (hydrogen content 0.3 wt.%), 1000 ppm of platinum catalyst, and 150 ppm of 3-methyl-1-penten-4-yn-3-ol. The specific surface area of the graphene foam film is 1000 m². 2 / g, with mesopores having a pore size of 2~50nm accounting for 60% of the volume, an area of 150×150mm, a thickness of 250μm, and an areal density of 35mg / cm³. 2 The aramid nanofibers are Kevlar 49 (400D), with a diameter of 150 nm, an aspect ratio of 3000:1, and a specific surface area of 400 m². 2 / g.
[0041] The preparation method of this graphene thermal pad includes the following steps: (I) Plasma cleaning Activated graphene foam films were obtained by plasma cleaning of the surfaces of N graphene foam films until Ra ≤ 50%. The cleaning was performed using a plasma cleaner with an Ar / O2 volume ratio of 8:1, an RF power of 180W, a gas pressure of 120Pa, a cleaning time of 35s, and a water-cooled backplate temperature of <80℃.
[0042] (II) Impregnated aramid nanofiber dispersion 2.0 g of aramid nanofibers, 1.2 g of potassium hydroxide, and 100 mL of dimethyl sulfoxide were reacted at 80 °C for 5 days to obtain a dispersion with a concentration of 20 mg / mL. The dispersion was diluted with dimethyl sulfoxide to obtain a first aramid nanofiber dispersion with a concentration of 0.30 mg / mL and a second aramid nanofiber dispersion with a concentration of 2.0 mg / mL. 600 activated graphene foam films were immersed in the first aramid nanofiber dispersion for 20 s to obtain a first impregnated graphene foam film. The remaining 100 activated graphene foam films were immersed in the second aramid nanofiber dispersion for 40 s, and this immersion was repeated three times to obtain a second impregnated graphene foam film.
[0043] (III) Drying and shaping The first and second impregnated graphene foam films were freeze-dried at -45°C for 8 hours, and then imidized at 250°C under a nitrogen atmosphere for 2.0 hours to obtain the first composite graphene foam film and the second composite graphene foam film, respectively.
[0044] (IV) Stacking and curing Vinyl-terminated silicone oil, hydrogen-containing silicone oil, platinum catalyst, and 3-methyl-1-penten-4-yn-3-ol were mixed and degassed to a silica liquid with a viscosity of 5200 cps. The silica liquid was then applied to both surfaces of each first and second composite graphene foam film using a scraper, with a wet thickness of 100 µm. Sixty hundred first composite graphene foam films were then stacked along opposite directions to obtain a first intermediate. One hundred second composite graphene foam films were divided into two equal parts and stacked at both ends of the first intermediate along the same stacking direction. The mixture was first heated to 90°C and held at 110 psi for 0.5 h, then heated to 130°C and held at 130 psi for 2.0 h, and then heated to 160°C and held for 45 min while maintaining pressure to obtain the second intermediate.
[0045] (V) Z-axis cutting The second intermediate was cut with diamond wire parallel to the stacking direction and then polished to a thickness of 0.5 mm for the graphene thermal pad. The diamond wire diameter was 0.30 mm, the particle size was 60 μm, the cutting speed was 0.4 mm / min, and the tension was 25 N.
[0046] Example 3 This embodiment is a graphene thermal conductive pad comprising 500 stacked composites. Each composite is formed by stacking a first silicone layer, a composite graphene foam film, and a second silicone layer. The composite graphene foam film is a graphene foam film with aramid nanofibers adsorbed onto its framework. Along the stacking direction of the composites, the content of aramid nanofibers in the 450 composites located in the middle is lower than that in the composites at both ends. The raw materials for the first and second silicone layers include 15 parts of vinyl-terminated silicone oil (viscosity 450 cps), 5 parts of hydrogen-containing silicone oil (hydrogen content 0.3 wt.%), 1000 ppm of platinum catalyst, and 80 ppm of 3-methyl-1-penten-4-yn-3-ol. The specific surface area of the graphene foam film is 1000 m². 2 / g, with a volume fraction of 65% being mesopores with a pore size of 2~50nm, an area of 150×150mm, a thickness of 300μm, and an areal density of 30mg / cm³. 2 The aramid nanofibers are Kevlar 49 (400D), with a diameter of 35 nm, an aspect ratio of 3000:1, and a specific surface area of 200 m². 2 / g.
[0047] The preparation method of this graphene thermal pad includes the following steps: (I) Plasma cleaning Activated graphene foam films were obtained by plasma cleaning of the surfaces of N graphene foam films until Ra ≤ 50%. The cleaning was performed using a plasma cleaner with an Ar / O2 volume ratio of 8:1, an RF power of 150W, a gas pressure of 180Pa, a cleaning time of 25s, and a water-cooled backplate temperature of <80℃.
[0048] (II) Impregnated aramid nanofiber dispersion A 20 mg / mL dispersion was obtained by reacting 2.0 g of aramid nanofibers, 1.2 g of sodium hydroxide, and 100 mL of ethanol-water (9:1 ratio) at 50 °C for 4 days. The dispersion was then diluted with dimethyl sulfoxide to obtain a first aramid nanofiber dispersion with a concentration of 0.15 mg / mL and a second aramid nanofiber dispersion with a concentration of 3.0 mg / mL. 450 activated graphene foam films were immersed in the first aramid nanofiber dispersion for 20 s to obtain a first impregnated graphene foam film. The remaining 50 activated graphene foam films were immersed in the second aramid nanofiber dispersion for 60 s, and this immersion was repeated three times to obtain a second impregnated graphene foam film.
[0049] (III) Drying and shaping The first and second impregnated graphene foam films were freeze-dried at -50°C for 10 hours, and then imidized at 280°C in an argon atmosphere for 1 hour to obtain the first composite graphene foam film and the second composite graphene foam film, respectively.
[0050] (IV) Stacking and curing Vinyl-terminated silicone oil, hydrogen-containing silicone oil, platinum catalyst, and 3-methyl-1-penten-4-yn-3-ol were mixed and degassed to a silica gel solution with a viscosity of 6500 cps. The silica gel solution was then applied to both surfaces of each first and second composite graphene foam film using a scraper, with a wet thickness of 120 µm. 450 first composite graphene foam films were then stacked along opposite directions to obtain a first intermediate. 50 second composite graphene foam films were divided into two equal parts and stacked at both ends of the first intermediate along the same stacking direction. The mixture was first heated to 70°C and held at 120 psi for 2.0 h, then heated to 125°C and held at 135 psi for 2.5 h, and finally heated to 160°C and held at 165 psi for 30 min to obtain the second intermediate.
[0051] (V) Z-axis cutting The second intermediate was cut with diamond wire parallel to the stacking direction and then polished to a thickness of 0.3 mm for the graphene thermal pad. The diamond wire diameter was 0.20 mm, the particle size was 40 μm, the cutting speed was 0.6 mm / min, and the tension was 15 N.
[0052] Comparative Example 1 This comparative example is a graphene thermal pad comprising 500 stacked composites. The composite is composed of a first silicone layer, a graphene foam film, and a second silicone layer. The raw materials for the first and second silicone layers include 25 parts of vinyl-terminated silicone oil (viscosity 350 cps), 3 parts of hydrogen-containing silicone oil (hydrogen content 0.5 wt.%), 1200 ppm platinum catalyst, and 100 ppm 2-methyl-3-butyn-2-ol. The graphene foam film has a specific surface area of 620 m². 2 / g, with mesopores having a pore size of 2~50nm accounting for 67% of the volume, an area of 150×150mm, a thickness of 180μm, and an areal density of 26mg / cm³. 2 .
[0053] The preparation method of this graphene thermal pad includes the following steps: (I) Plasma cleaning Activated graphene foam films were obtained by plasma cleaning of the surfaces of N graphene foam films until Ra ≤ 50%. The cleaning was performed using a plasma cleaner with an Ar / O2 volume ratio of 5:1, an RF power of 100W, a gas pressure of 80Pa, a time of 15s, and a water-cooled backplate temperature of <80℃.
[0054] (II) Stacking and curing Vinyl-terminated silicone oil, hydrogen-containing silicone oil, platinum catalyst, and 2-methyl-3-butyn-2-ol were mixed and degassed to a silica liquid with a viscosity of 4820 cps. The silica liquid was then applied to both surfaces of each graphene foam film using a scraper to a wet thickness of 80 µm. 450 graphene foam films were then stacked along opposite directions to obtain the first intermediate. The remaining 50 graphene foam films were divided into two equal parts and stacked at both ends of the first intermediate along the same stacking direction. The mixture was first heated to 80°C and held at 100 psi for 1.0 h, then heated to 120°C and held at 150 psi for 1.0 h, and then heated to 150°C and held for 30 min while maintaining pressure to obtain the second intermediate.
[0055] (III) Z-axis cutting The second intermediate was cut with diamond wire parallel to the stacking direction and then polished to a thickness of 0.3 mm to form a graphene thermal pad. The diamond wire diameter was 0.20 mm, the particle size was 50 μm, the cutting speed was 0.5 mm / min, and the tension was 20 N.
[0056] Comparative Example 2 This comparative example is a graphene thermal conductive pad comprising 500 stacked composites. The composite is composed of a first silicone layer, a composite graphene foam film, and a second silicone layer. The composite graphene foam film is a graphene foam film with aramid nanofibers adsorbed onto its framework. The raw materials for the first and second silicone layers include 25 parts of vinyl-terminated silicone oil (viscosity 350 cps), 3 parts of hydrogen-containing silicone oil (hydrogen content 0.5 wt.%), 1200 ppm platinum catalyst, and 100 ppm 2-methyl-3-butyn-2-ol. The specific surface area of the graphene foam film is 620 m². 2 / g, with mesopores having a pore size of 2~50nm accounting for 67% of the volume, an area of 150×150mm, a thickness of 180μm, and an areal density of 26mg / cm³. 2 The aramid nanofibers are Kevlar 49 (400D), with a diameter of 50 nm, an aspect ratio of 2000:1, and a specific surface area of 350 m². 2 / g.
[0057] The preparation method of this graphene thermal pad includes the following steps: (I) Plasma cleaning Activated graphene foam films were obtained by plasma cleaning of the surfaces of N graphene foam films until Ra ≤ 50%. The cleaning was performed using a plasma cleaner with an Ar / O2 volume ratio of 5:1, an RF power of 100W, a gas pressure of 80Pa, a time of 15s, and a water-cooled backplate temperature of <80℃.
[0058] (II) Impregnated aramid nanofiber dispersion 2.0 g of aramid nanofibers, 1.2 g of potassium hydroxide, and 100 mL of dimethyl sulfoxide were reacted at 80 °C for 5 days to obtain a dispersion with a concentration of 20 mg / mL. The dispersion was then diluted with dimethyl sulfoxide to obtain an aramid nanofiber dispersion with a concentration of 1.8 mg / mL. An activated graphene foam film was then immersed in the aramid nanofiber dispersion for 60 s, and this immersion was repeated twice to obtain an impregnated graphene foam film.
[0059] (III) Drying and shaping After the impregnated graphene foam film was freeze-dried at -45℃ for 18 hours, it was then imidized at 200℃ under a nitrogen atmosphere for 1.5 hours to obtain a composite graphene foam film.
[0060] (IV) Stacking and curing Vinyl-terminated silicone oil, hydrogen-containing silicone oil, platinum catalyst, and 2-methyl-3-butyn-2-ol were mixed and degassed to a silica liquid with a viscosity of 4820 cps. The silica liquid was then applied to both surfaces of each composite graphene foam film using a doctor blade to a wet thickness of 80 µm. Five hundred composite graphene foam films were then stacked along opposite surfaces to obtain the first intermediate. The mixture was first heated to 80°C and held at 100 psi for 1.0 h, then heated to 120°C and held at 150 psi for 1.0 h, and then, while maintaining pressure, heated to 150°C and held for 30 min to obtain the second intermediate.
[0061] (V) Z-axis cutting The second intermediate was cut with diamond wire parallel to the stacking direction and then polished to a thickness of 0.3 mm to form a graphene thermal pad. The diamond wire diameter was 0.20 mm, the particle size was 50 μm, the cutting speed was 0.5 mm / min, and the tension was 20 N.
[0062] The graphene thermal pads prepared in Examples 1-3 and Comparative Examples 1-2 were subjected to performance tests under the following conditions, and the test results are shown in Table 1.
[0063] Thermal conductivity was tested according to ASTM D5470. Interlaminar tensile strength was tested according to ASTM D412. Compression ratio at 50 psi was tested according to ASTM D575. Cutting yield was calculated based on appearance statistics per 1000 pieces.
[0064] Table 1. Performance test results of graphene thermal pads prepared in Examples 1-3 and Comparative Examples 1-2
[0065] As shown in Table 1, in Examples 1-3, impregnating graphene foam film with aramid nanofiber dispersion and using gradient impregnation can make graphene thermal pads simultaneously achieve good thermal conductivity, compression resilience, strength, and cutting yield.
[0066] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A graphene thermally conductive pad, characterized in that, The system comprises N stacked composites, where N is an integer greater than or equal to 100. Each composite is formed by stacking a first silicone layer, a composite graphene foam film, and a second silicone layer. The composite graphene foam film is a graphene foam film with aramid nanofibers adsorbed on its framework. Along the stacking direction of the composites, the content of aramid nanofibers in the M middle composites is lower than that in the composites at both ends, where M is an integer from 0.80 to 0.95 times N.
2. The graphene thermal pad according to claim 1, characterized in that, The first silicone layer and the second silicone layer have the same composition, and the raw materials include 15-40 parts of vinyl silicone oil, 2-8 parts of hydrogen-containing silicone oil, 500-2000 ppm of platinum catalyst and 50-200 ppm of inhibitor.
3. The graphene thermal pad according to claim 2, characterized in that, The vinyl silicone oil is a vinyl-terminated silicone oil with a viscosity of 200-500 cps, the hydrogen content of the hydrogen-containing silicone oil is 0.3-0.6 wt.%, and the inhibitor is selected from at least one of 2-methyl-3-butyn-2-ol, 3,5-dimethyl-1-hexyn-3-ol, 2-phenyl-3-butyn-2-ol, 1-ethynylcyclohexanol, 3-methyl-1-penten-4-yn-3-ol, and 3,5-dimethyl-3-hexen-1-yn.
4. The graphene thermal pad according to claim 1, characterized in that, The specific surface area of the graphene foam film is 300~1200m². 2 / g, with a volume fraction of mesopores of ≥60% having a pore size of 2~50nm, a thickness of 100~500μm, and an areal density of 10~50mg / cm³. 2 .
5. The graphene thermal pad according to claim 1, characterized in that, The aramid nanofibers have a diameter of 10-100 nm, an aspect ratio of 1000-5000:1, and a specific surface area of 50-600 m². 2 / g.
6. The graphene thermal pad according to claim 1, characterized in that, Z-direction thermal conductivity ≥130W / m·K, interlaminar tensile strength ≥0.06MPa, compression ratio at 50psi ≥40%, and overall cutting yield ≥98%.
7. A method for preparing a graphene thermally conductive pad, characterized in that, Including the following steps: (I) Plasma cleaning The surfaces of N graphene foam films are plasma cleaned until Ra≤50% to obtain activated graphene foam films, where N is an integer greater than or equal to 100. (II) Impregnated aramid nanofiber dispersion First, a first aramid nanofiber dispersion with a concentration of 0.05~0.50 mg / mL and a second aramid nanofiber dispersion with a concentration of 1.5~3.0 mg / mL are prepared. M activated graphene foam films are impregnated in the first aramid nanofiber dispersion to obtain a first impregnated graphene foam film. The remaining activated graphene foam films are impregnated in the second aramid nanofiber dispersion to obtain a second impregnated graphene foam film. M is an integer multiple of N, ranging from 0.80 to 0.
95. (III) Drying and shaping The first impregnated graphene foam film and the second impregnated graphene foam film were freeze-dried and then heat-treated to obtain the first composite graphene foam film and the second composite graphene foam film, respectively. (IV) Stacking and curing Both surfaces of each of the first composite graphene foam films and each of the second composite graphene foam films are coated with silicone liquid. Then, all the first composite graphene foam films are stacked along the opposite direction of the surfaces to obtain a first intermediate body. All the second composite graphene foam films are divided into two parts and stacked on both ends of the first intermediate body along the same stacking direction. Then, they are hot-pressed and cured to obtain a second intermediate body. (V) Z-axis cutting The second intermediate is cut along a direction parallel to the stacking direction to obtain a graphene thermal pad.
8. The method for preparing the graphene thermal pad according to claim 7, characterized in that, Includes at least one of the following features (1) to (9): (1) The specific surface area of the graphene foam film is 300~1200m². 2 / g, with a volume fraction of mesopores of ≥60% having a pore size of 2~50nm, a thickness of 100~500μm, and an areal density of 10~50mg / cm³. 2 ; (2) The plasma cleaning is carried out using a plasma cleaning machine. The volume ratio of Ar / O2 in the plasma cleaning machine is 5~10:1, the RF power is 50~200W, the gas pressure is 50~200Pa, the time is 5~30s, and the water-cooled back plate is <80℃. (3) The first aramid nanofiber dispersion and the second aramid nanofiber dispersion contain aramid nanofibers, solvent and inorganic alkali, with a size of 10~100 nm, an aspect ratio of 1000~5000:1, and a specific surface area of 50~600 m². 2 / g, wherein the solvent is an ethanol-water mixture, dimethyl sulfoxide, or dimethylformamide, the inorganic base is potassium hydroxide or sodium hydroxide, and the mass ratio of the inorganic base to the aramid nanofiber is 0.5~3.0:1; (4) The activated graphene foam film is immersed in the first ANF dispersion for 10-30s, and the activated graphene foam film is immersed in the second ANF dispersion for 30-90s and is repeatedly immersed 2-3 times. (5) The freeze-drying temperature is -50~-30℃ and the time is 6~24h; (6) The heat treatment is carried out in an inert atmosphere at a temperature of 200-280°C for 1-2 hours. (7) The hot pressing curing is a gradient temperature curing method. First, the temperature is raised to 70~100℃ and 80~120psi and held for 0.5~2.0h. Then, the temperature is raised to 110~135℃ and 130~160psi and held for 0.5~2.0h. The pressure is maintained and the temperature is raised to 140~160℃ and held for 15~60min. (8) The Z-axis cutting is performed using diamond wire cutting, wherein the wire diameter of the diamond wire cutting is 0.20~0.35mm, the particle size is 30~60μm, the speed is 0.3~0.8mm / min, and the tension is 15~25N; (9) After the Z-axis cutting, double-sided polishing is performed, and the polishing is performed until the thickness of the pad is 0.2~0.5mm.
9. The method for preparing the graphene thermal pad according to claim 7, characterized in that, The raw materials for the silicone liquid include 15-40 parts of vinyl silicone oil, 2-8 parts of hydrogen-containing silicone oil, 500-2000 ppm of platinum catalyst, and 50-200 ppm of inhibitor.
10. The method for preparing the graphene thermal pad according to claim 9, characterized in that, Includes at least one of the following features (a) to (c): (a) The vinyl silicone oil is a vinyl-terminated silicone oil with a viscosity of 200-500 cps, the hydrogen content of the hydrogen-containing silicone oil is 0.3-0.6 wt.%, and the inhibitor is selected from at least one of 2-methyl-3-butyn-2-ol, 3,5-dimethyl-1-hexyn-3-ol, 2-phenyl-3-butyn-2-ol, 1-ethynylcyclohexanol, 3-methyl-1-penten-4-yn-3-ol, and 3,5-dimethyl-3-hexen-1-yne; (B) The viscosity of the silica gel liquid at 25°C is 2000~8000 cps; (c) The silicone liquid is applied to both surfaces of the first composite graphene foam film or the second composite graphene foam film by a doctor blade or a micro-gravure roller, with a wet thickness of 20~200μm.